Technical Considerations of Giant Right Coronary Artery Aneurysm Exclusion - James Barr; Metesh Nalin Acharya; Antonios Kourliouros; Shahzad Gull Raja (Case Reports in Surgery)
Giant coronary artery aneurysms are rare clinical entities. We report the case of a 49-year-old man who presented with dyspnoea and exertional chest pain. Investigations confirmed an aneurysmal right coronary artery measuring 4 cm with a fistulous communication to the right atrium. Following right atriotomy, the fistula was oversewn and the aneurysmal right coronary artery ligated at its origin and at several points along its course. A saphenous vein graft was anastomosed to the posterior descending artery. Persistent ventricular fibrillation occurred upon chest closure, attributed to ischaemia following ligation of the aneurysmal coronary artery. Emergent resternotomy and internal defibrillation were successfully performed. The sternum was stented open to reduce right ventricular strain and closed the following day. The patient made an unremarkable recovery. We here address the technical challenges associated with surgical repair of right coronary aneurysms and the physiology and management of potential complications.